Skip-beat!. 5 - Nakamura, Yoshiki (Shojo beat manga., 2007)
Now that Kyoko Mogami's true love Sho has made it big as an idol, he's dumping her. Determined to beat Sho in show business, Kyoko lands a role in a TV show as a giant chicken and then tries out for a big commercial. There she meets her love rival Moko, who's having rival woes of her own. Can Kyoko and Moko overcome their differences to act as a team? By the creator of Tokyo Crazy Paradise.